A relational view of climate adaptation in the private sector: How do value chain interactions shape business perceptions of climate risk and adaptive behaviours?. (10th September 2019) - Canevari‐Luzardo, Laura M.; Berkhout, Frans; Pelling, Mark
Abstract: Studies exploring climate change adaptation in the private sector have seldom investigated the effect of business network interactions on climate vulnerability and adaptation outcomes. This paper proposes a novel theoretical framework to explore how business–network dynamics affect risk perceptions and adaptive behaviours in business firms. The framework is empirically grounded in a comparative analysis of business–network dynamics from three agricultural value chains in Jamaica that are vulnerable to climate change impacts. The results illustrate how the exposure, sensitivity, and adaptive capacity of value chain actors are influenced by business interdependencies and interfirm relationships. We find that the level of formality of business exchanges (contractual or noncontractual), the level of resource interdependency, and the ability to diversify access channels to critical resources can influence the propagation of climate‐related risks and influence actors' exposure and sensitivity to those risks. The study also offers evidence of the role played by bonding and bridging relational ties on adaptive capacity. The framework and findings provide a foundation for a new research agenda exploring a relational view of firm adaptation strategy in response to climate risks.